Cost-Effective Media for Production of Lactic Acid Bacteria Isolated from Poultry in Kuwait - Almansour , Hamad; Alonaizi, Thnayan; Kishk, Mohamed; Hadi, Ahmad; Alsurrayai, Tahani; Alawadi, Mohamed; Varughese, Siby (International Journal of Poultry Science, 2019)
Background and Objective: Poultry is a primary source of meat in Kuwait. Abuse of antibiotics in the poultry industry can lead to unfavorable effects on food safety. However safer approaches, such as probiotic use, can be expensive. The present study screened cost-effective media formulations which support growth of lactic acid bacteria. Materials and Methods: Shake flask experiments were conducted using three bacterial strains isolated from Kuwaiti poultry farms (Lactobacillus brevis, Lactobacillus parabuchneri and Pediococcus pentosaceus). Ten media formulations containing different concentrations of tomato serum, molasses and yeast extract were inoculated with bacteria and incubated at 30, 35, or 37°C. Samples were taken periodically (0, 24 and 48 h), plated on selective agar and incubated overnight; growth was measured the next day. Statistical analysis revealed the formulation that supports the highest growth when compared to de Man Rogosa and Sharpe medium. Results: The formulation containing 5 g L–1 yeast extract, 200 mL L–1 tomato serum and 10 g L–1 molasses resulted in the best overall growth and supported a longer exponential phase compared to the commercial medium. Conclusion: This new media could be used as a cost-effective alternative for large-scale production of certain poultry probiotics.